2018
DOI: 10.1038/s41598-018-27335-y
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation of Focused Ultrasound-Facilitated Drug Delivery for the Treatment of Leptomeningeal Metastases

Abstract: Leptomeningeal metastases (LM) are a serious complication of cancer in the central nervous system (CNS) and are diagnosed in approximately 5% of patients with solid tumors. Effective treatment using systemically administered therapeutics is hindered by the barriers of the CNS. Ultrasound can mediate delivery of drugs through these barriers. The goal of this study was to test the feasibility of using ultrasound-mediated drug delivery to improve the treatment of LM. LM was induced in the spinal cord of athymic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…MRgFUS blood-spinal cord barrier opening has not yet been developed in humans, but has been performed safely in the spinal cord of non-ALS rodent models 42,43 . An early study demonstrated enhanced chemotherapy delivery using MRgFUS blood-spinal cord barrier opening in rodents 44 . However, the bony vertebrae of the spinal column in primates present a technical challenge for focusing the ultrasound and further validation and optimization studies are necessary before translation to humans 45 .…”
Section: Discussionmentioning
confidence: 99%
“…MRgFUS blood-spinal cord barrier opening has not yet been developed in humans, but has been performed safely in the spinal cord of non-ALS rodent models 42,43 . An early study demonstrated enhanced chemotherapy delivery using MRgFUS blood-spinal cord barrier opening in rodents 44 . However, the bony vertebrae of the spinal column in primates present a technical challenge for focusing the ultrasound and further validation and optimization studies are necessary before translation to humans 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The issue of target motion due to breathing is reduced by placing the animals supine so that the chest can expand freely however, the posterior elements of the vertebral bone are highly irregular especially in comparison to the skull surface. In rats, an average of about a 33% signal loss is expected from bone attenuation, although with large spatial variations 21 , but large focal distortions are not expected since the vertebrae are thin. It was expected that using the same controller for this study as used in the small animal BBB studies would provide similar opening.…”
Section: Discussionmentioning
confidence: 99%
“…Pressure values were based off of calibrations performed in water and were not de-rated for attenuation through tissue. Mean transmission in rat spines at 0.5 MHz has previously been reported as 67 ± 15% (range: 45–92%) and is subject to large local variations due to the bony anatomy of the spine 21 . The signal level to trigger the controller was calculated as the baseline signal plus 10 times the standard deviation of the baseline signal.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…FUS has been used to increase the vascular permeability and deliver a variety of therapeutics in different types of preclinical disease models. To date, the application of FUS-mediated BBB modulation for drug delivery against tumors has been applied across many locations in the CNS such as cerebrum, brain stem, and spine [ 81 , 82 , 83 ]. This technique has been used to enhance the delivery of a wide range of chemotherapeutic agents such as doxorubicin, carboplatin, and temozolomide across the BBB/BBTB.…”
Section: Preclinical Tumor Studiesmentioning
confidence: 99%